Cell cycle inhibitors for the treatment of NSCLC. (May 2014) - Shcherba, Marina; Liang, Yuanxin; Fernandes, David; Perez-Soler, Roman; Cheng, Haiying
<x xml:space="preserve">Abstract</x> Introduction: Lung cancer remains to be the leading cause of cancer-related death worldwide. Treatment of lung cancer still poses a significant challenge. Cell cycle is a tightly integrated process and is frequently aberrant in lung cancer. Cell cycle inhibitors have emerged as novel therapeutics, in anticipation of overcoming the unrestricted cell division and growth in lung cancer. Areas covered: In this article, we first address the potential roles of cell cycle proteins and cell cycle deregulation in the development of lung cancer. The review then provides an overview for several major categories of cell cycle inhibitors with particular attention to their tolerability and disease control in early phases of lung cancer trials. Expert opinion: Targeted agents against different components of cell cycle regulation, such as cyclin-dependent kinase, polo-like kinase, checkpoint kinase and aurora kinase, are currently in clinical development for lung cancer management. Their clinical benefits remain to be defined. When evaluated as single agents in lung cancer, cell cycle inhibitors are often associated with limited clinical activity and tolerable toxicities. The key challenges in the drug development are to understand resistance mechanisms and to identify predictive biomarkers that can potentially guide patient selection and optimize the utility of these targeted inhibitors.